2021
DOI: 10.1101/2021.09.10.459444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transplantation of bacteriophages from ulcerative colitis patients shifts the gut bacteriome and exacerbates severity of DSS-colitis

Abstract: Inflammatory bowel diseases (IBDs) including Crohn's disease (CD) and ulcerative colitis (UC) are characterized by chronic and debilitating gut inflammation. Altered bacterial communities of the intestine are strongly associated with IBD initiation and progression. The gut virome, which is primarily composed of bacterial viruses (bacteriophages, phages) is thought to be an important factor regulating and shaping microbial communities in the gut. While alterations in the gut virome have been observed in IBD pat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…In the research process, full consideration should be given to the research in different animals and populations to achieve more precise intervention effects (Ni et al, 2023). Apart from bacteria, virus and fungi also play a vital role in IBD, which regulating and shaping microbial communities in the gut (Federici et al, 2022;Sinha et al, 2022). Therefore, it is a direction to find further relationship between virus and fungi and intestinal flora to expect for new therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In the research process, full consideration should be given to the research in different animals and populations to achieve more precise intervention effects (Ni et al, 2023). Apart from bacteria, virus and fungi also play a vital role in IBD, which regulating and shaping microbial communities in the gut (Federici et al, 2022;Sinha et al, 2022). Therefore, it is a direction to find further relationship between virus and fungi and intestinal flora to expect for new therapies.…”
Section: Discussionmentioning
confidence: 99%
“… 84 A recent preprint study observed that transplantation of VLPs from UC patient faeces to human-microbiota-associated (HMA) mice significantly aggravated colitis in mice and changed the bacterial taxa associated with IBD pathogenesis. 8 In another murine study, several phage taxa belonging to Caudovirales were shown to mediate TLR9-dependent activation of CD4 + T cells to exacerbate intestinal inflammation, by enhancing the TLR-dependent production of IFN-γ. 71 Together, these results emphasised the potential central role of phages in activating the gut mucosal immune responses and exacerbating colitis.…”
Section: The Gut Virome In Human Diseasesmentioning
confidence: 99%
“… 6 The human virome is composed of eukaryotic and prokaryotic viruses, including viruses that infect human cells, viruses that infect microbes (such as bacteria, fungi, and archaea), and plant viruses that are primarily derived from environment and diet. 7 Akin to the bacterial microbiome (bacteriome), the gut virome also plays an important role in the pathogenesis of disease, including inflammatory bowel disease (IBD), 8 Clostridioides difficile infection (CDI), 9 obesity, 10 diabetes, SARS-CoV-2 infection, 11 , 12 liver diseases, 13 colorectal cancer (CRC), 14 as well as malnutrition. 15 Gut virome rectification has shown great potential as disease therapeutics through faecal microbiota transplantation (FMT), faecal virome transplantation (FVT), and phage therapy.…”
Section: Introductionmentioning
confidence: 99%